Soybean Cost-Return Budget in North Central Kansas - O'Brien, Daniel M.; Duncan, Stewart R.; Olson, Brian L.S. (My University, 2011)
This publication provides estimated cost and returns for forward farm planning for soybeans in north central Kansas.
MF2160_2011_12
Keywords: MF2160; Crops; Economics; MF